Severe acute heart failure - experimental model with very low mortality - Lacko, Stanislav; Mlček, Mikuláš; Hála, Pavel; Popková, Michaela; Janák, David; Hrachovina, Matěj; Kudlička, Jaroslav; Hrachovina, Vladimír; Ošťádal, Petr; Kittnar, Otomar (Physiological research, 2018)
The growth in the experimental research of facilities to support extracorporeal circulation requires the further development of models of acute heart failure that can be well controlled and reproduced. Two types of acute heart failure were examined in domestic pigs (Sus scrofa domestica): a hypoxic model (n=5) with continuous perfusion of the left coronary artery by hypoxic deoxygenated blood and ischemic model (n=9) with proximal closure of the left coronary artery and controlled hypoperfusion behind the closure. The aim was a severe, stable heart pump failure defined by hemodynamic parameters changes: a) decrease in cardiac output by at least 50 %; b) decrease in mixed venous blood saturation to under 60 %; c) left ventricular ejection fraction below 25 %; and d) decrease in flow via the carotid arteries at least 50 %. Acute heart failure developed in the first group in one animal with no acute mortality and in the second group in 8 animals with no acute mortality. In the case of ischemic model the cardiac output fell from 6.70+/-0.89 l/min to 2.89+/-0.75 l/min. The saturation of the mixed venous blood decreased from 83+/-2 % to 58+/-8 %. The left ventricular ejection fraction decreased from 50+/-8 % to 19+/-2 %. The flow via the carotid arteries decreased from 337+/-78 ml/min to 136+/-59 ml/min (P</=0.001 for all comparisons). The proposed ischemic model is not burdened with acute mortality in the development of heart failure and is suitable for further use in experimental research into extracorporeal circulatory support.
Keywords: stupeň závažnosti nemoci; Heart Failure; Animals; Hemodynamics; hemodynamika; akutní nemoc; srdeční selhání; Acute Disease; zvířata; Female; Severity of Illness Index; Disease Models, Animal; modely nemocí na zvířatech; prasata; Swine; ženské pohlaví; Sus scrofa